EFEKTIVITAS BERBAGAI AGENS HAYATI DALAM MENINGKATKAN PERTUMBUHAN TANAMAN TOMAT (Lycopersicum esculentum Mill.) - ARIANI, RETNO WULAN; BAHRUN, ANDI; HASID, RACHMAWATI; SUTARIATI, GUSTI AYU KADE (Jurnal Agroteknos, 2022)
The research aims to determine the effectiveness of various biological agents in increasing the growth of tomato plants. The study used a randomized block design, consisting of 10 treatments, namely without the use of biological agents, Pseudomonas sp. SWRIIA02, Bacillus sp. CKD061, Pseudomonas sp. Ab06, Pseudomonas sp. Bb05, SWRIIA02 + CKD061, Ab06 + CKD061, Bb05 + CKD061, SWRIIA02 + CKD061 and SWRII02 + CKD061 + Bb05 and each treatment was repeated 3 times. The results showed that the treatment of biological agents had a very significant effect on plant height 14 DAP, number of leaves 12 DAP, plant dry weight and significantly affected plant height 28 DAP, 42 DAP, stem diameter 42 DAP, root fresh weight, root dry weight and length root. The biological agent Pseudomonas sp. SWRIIA02, Bb05+CKD061, Bacillus sp. CKD061, SWRIIA02+CKD061+Bb05 were better at increasing the growth of local tomato plants compared to those without biological agents, with the percentage increase in plant dry weight in each of these treatments reaching 62.30%, 58.78%, 55.91% and 51.76% which was not significantly different from other treatments but significantly different from the treatment without biological agents.